Hire purchase in a free society - Harris, Ralph; Seldon, Arthur (London : Institute of Economic Affairs, 1961)
In earlier ages when mankind eked out a bare existence with nothing in hand beyond that needed to sustain life, governments did not have to worry about hire purchase.
includes index
Includes bibliographies.
ii 18/01/2019
Loans
Keywords: Installment plan; Commercial finance companies